Exploring Artificial Intelligence in Academic Essay: Higher Education Student's Perspective - Agung Rinaldy Malik; Yuni Pratiwi; Kusubakti Andajani; I Wayan Numertayasa; Sri Suharti; Arisa Darwis; Marzuki (International Journal of Educational Research Open, 2023)
Artificial Intelligence (AI) and academic essay writing merge to create a transformative intersection in education, each reciprocally refining and reforming the other. AI, through its innovative technologies and flexible learning strategies, elevates academic writing by offering dynamic, interactive learning settings, and personalized educational journeys. This study aimed to explore students' perceptions of AI usage in academic essay writing using a case study design. It involved 245 undergraduate students from 25 tertiary institutions in Eastern and Central Indonesian provinces, with data collected via Google form to gain insights into students' attitudes toward AI tools in writing academic essays. Findings indicated a positive reception of AI-powered writing tools, with students acknowledging their benefits in grammar checks, plagiarism detection, language translation, and essay outlines. AI was found to enhance students' writing abilities, self-efficacy, and understanding of academic integrity. However, some students expressed concerns about potential impacts on creativity, critical thinking, and ethical writing practices. The study emphasized a balanced approach to AI integration, where AI collaborates with human authors, and also identified popular AI tools used by Indonesian students. As such, the research highlighted AI's significant role in supporting academic writing while preserving human creativity and critical thinking, underscoring the importance of maintaining a balanced integration to sustain human ingenuity and critical thought in academic discourse.